Influence of altitude on soil organic carbon stocks in land use systems of Uttarakhand State: Geospatial approach - GAHALOD, N. S.; JARYAL, NAVNEET; ROODAGI, MALLIKARJUN; DHALE, S. A. (Journal of Soil and Water Conservation, 2018)
The Soil Organic Carbon (SOC) stock of soil plays an important role in mitigating the effect of climate change. The soils capacity to the atmospheric carbon depends upon climate, land use and altitude of area. The present study was conducted to estimate the SOC stocks (0-25 cm soil) along the altitudinal gradient viz., low mountain (2500m) in associated forest, agricultural, plantations and grass land/open scrub land uses in Uttarakhand state using geospatial technique. Altitudinal zone had observed to have strong influence on the distribution of SOC stock in the state. Study confirms that upper mountain areas hold SOC stocks ranging from 51to 160 t C ha-1. This can be attributed to the fact that whole of the studied area in upper mountains falls under forests and grasslands/ open scrub. In general, forest and grassland/open scrub had recorded SOC stock >51 t C ha-1 (72.7% of forest area and 77.7% area under grassland/open scrub) as compared to agriculture (18.6% of agriculture land).